2014
DOI: 10.4103/0189-6725.143136
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in managing paediatric osteomyelitis in the developing world: Analysis of cases presenting to a tertiary referral centre in Tanzania

Abstract: This is, to the best of our knowledge, the second largest study of paediatric osteomyelitis in the developing world. Major challenges facing this centre include a lack of availability of bacterial cultures and failure to attend follow-up. Delayed presentation of osteomyelitis to our centre is associated with recurrence of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 7 publications
(9 reference statements)
3
17
1
Order By: Relevance
“…As shown in previous studies, the tibia is the most commonly affected bone [2, 6, 10, 14, 26] followed by the femur and the humerus. The tibia also had the most number of bone defects (B4 classifications) (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…As shown in previous studies, the tibia is the most commonly affected bone [2, 6, 10, 14, 26] followed by the femur and the humerus. The tibia also had the most number of bone defects (B4 classifications) (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…The accurate documentation of follow-up is variable. Inconsistent follow-up is highlighted in another recent study that had a 47 % rate of patients who failed to attend follow-up [14]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above-mentioned etiologic factors, cranial osteomyelitis is influenced by systemic diseases that decrease bone vascularity, the course of illness, and alter the host defense mechanism. [ 12 22 48 49 50 51 52 53 54 55 56 57 58 ] The causative infections and predisposing comorbidities are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…12 Result of our study about the common site of chronic infection was similar with Kubwimana study that reported tibia with frequency 35% because tibia is subcutaneous anteriorly and not fully covered by muscles and thus more prone to open fractures. 13,14 This study had certain limitations, for example, diabetic foot infection cases were not treated at the departments, and complete follow-up data was not available, which impacted the observation of the overall distribution of osteomyelitis. Information about the influential factors was incomplete.…”
Section: Discussionmentioning
confidence: 99%